Divine Blueprints & Unseen Realities: A Comparative Study of Plato's Forms and Islamic Metaphysics (Al-Aasar, 2025)
This study is a comparative metaphysical study of the Theory of Forms by Plato and the Islamic concept of the Unseen (al-Ghaib), as they both present the ontological basis of reality in the form of Divine Blueprints. Attempting to unite the Platonic domain of Eide (Forms) and the Islamic metaphysics, the research examines the way in which these traditions postulate a primary, intelligible realm that exists before, and determines the secondary, material world. To start with, the investigation explores the work by Plato, the Timaeus, where the world of becoming is introduced as a conscious simulation of a perennial prototype. This is compared with the Islamic idea of al-Ghaib, which is interpreted in the works of Seyyed Hossein Nasr and Abul Aaala Mawdudi, where structural analogies of the Platonic archetypes are found in the Islamic al-ayan al-thabitah (permanent archetypes). Although both systems make use of an ontological hierarchy to explain the derivative nature of the sensible world, the paper finds a fundamental difference in teleology and origin: in which Plato considers the Forms to exist as an independent metaphysical entity, whereas Islamic metaphysics locates all of the unseen realities within Tawhid (Divine Unity) such that the blueprint is an expression of Divine Sovereignty and not an abstract ideal. The paper concludes that even though Plato stresses an intellectual journey towards the Good, the Islamic paradigm incorporates these realities in a participatory paradigm of Khilafah (vicegerency). Finally, this paper states that the restoration of these metaphysical blueprints is the key to solving modern crises of meaning and ecological disturbance.